Hsa-miR-133a-3p, miR-1-3p, GOLPH3 and JUP combination results in a good biomarker to distinguish between prostate cancer and non-prostate cancer patients - Duca, Rocío Belén; Massillo, Cintia; Farré, Paula Lucía; Graña, Karen Daniela; Moro, Juana; Gardner, Kevin; Lacunza, Ezequiel; De Siervi, Adriana (Frontiers in Oncology, 2022)
The incidence and mortality of Prostate Cancer (PCa) worldwide correlate with age and bad dietary habits. Previously, we investigated the mRNA/miRNA role on PCa development and progression using high fat diet (HFD) fed mice. Here our main goal was to investigate the effect of HFD on the expression of PCa-related miRNAs and their relevance in PCa patients. We identified 6 up- and 18 down-regulated miRNAs in TRAMP-C1 mice prostate tumors under HFD conditions using miRNA microarrays. Three down-regulated miRNAs: mmu-miR-133a-3p, -1a-3p and -29c-3p were validated in TRAMP-C1 mice prostate tumor by stem-loop RT-qPCR. Hsa-miR-133a-3p/1-3p expression levels were significantly decreased in PCa compared to normal tissues while hsa-miR-133a-3p was found to be decreased in metastatic prostate cancer tumors compared to non-metastatic PCa. We examined the promoter region of hsa-miR-133a-3p/1-3p genes and compared methylation at these loci with mature miRNA expression. We found that hsa-miR-1-2/miR-133a-1 cluster promoter hypermethylation decreased hsa-miR-133a-3p/1-3p expression in PCa. GOLPH3 and JUP, two hsa-miR-133a-3p and miR-1-3p predicted target genes, were up-regulated in PCa. ROC analysis showed that the combination of hsa-miR-133a-3p, miR-1-3p, GOLPH3 and JUP is a promising panel biomarker to distinguish between PCa and NAT. These results link PCa aggressiveness to the attenuation of hsa-miR-133a-3p and miR-1a-3p expression by promoter hypermethylation. Hsa-miR-133a-3p and miR-1-3p down-regulation may enhance PCa aggressiveness in part by targeting GOLPH3 and JUP.